1989
DOI: 10.1111/j.1476-5381.1989.tb16878.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of anaesthetics and avermectin on GABAA chloride channels in mammalian dorsal root ganglion neurones

Abstract: 1 The y-aminobutyric acid (GABA)-mimetic actions of some anaesthetics and the antehelminthic avermectin B1a were examined on freshly isolated mammalian dorsal root ganglion (DRG) neurones by use of suction electrodes and a single electrode voltage clamp.2 Pentobarbitone (60yM-3mM), chloralose (600yM-1mM), etomidate (10-100 pM), alphaxalone (10-60pM) and avermectin (10-60pM) directly activated chloride channels in GABA-sensitive DRG neurones. The agonist action was sensitive to block by bicuculline and picrotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 28 publications
7
55
2
Order By: Relevance
“…The present study suggests that the blocking effect of propofol is independent of voltage. GABAA receptor block by pentobarbitone also appears to be independent of voltage (Robertson, 1989). Taken together, these observations suggest that GABAA receptor inhibition by these anaesthetics is not due to a channel block similar to that seen at the N-methyl-D-aspartate receptor with charged blocking compounds such as the dissociative anaesthetic, ketamine (Halliwell et al, 1989).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The present study suggests that the blocking effect of propofol is independent of voltage. GABAA receptor block by pentobarbitone also appears to be independent of voltage (Robertson, 1989). Taken together, these observations suggest that GABAA receptor inhibition by these anaesthetics is not due to a channel block similar to that seen at the N-methyl-D-aspartate receptor with charged blocking compounds such as the dissociative anaesthetic, ketamine (Halliwell et al, 1989).…”
Section: Discussionsupporting
confidence: 53%
“…Numerous other compounds with general anaesthetic properties potentiate the actions of GABA and at higher doses directly activate GABAA receptors. These agents include anaesthetic barbiturates (Macdonald et al, 1986), anaesthetic steroids (Cottrell et al, 1987;Harrison et al, 1987), etomidate (Robertson, 1989), chlormethiazole (Hales & Lambert, 1992) and volatile agents (Jones et al, 1992;Yang et al, 1992). The anticonvulsant and anxiolytic benzodiazepines are also potent potentiators of GABA-evoked responses, but are unable to activate directly GABAA receptors in the absence of GABA.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to another ligand gated ion channel, the nicotinic acetylcholine receptor, which is activated by physostigmine via a site separate from the acetylcholine binding site (Okonjo et al, 1991;Lena & Changeux, 1993). Krishek & Smart (1995) (Akaike et al, 1987;Peters, 1988;Robertson, 1989) have reported on the washout phenomenon observed with high concentrations of pentobarbitone. This effect, which has been termed 'bounce' or 'hump', involves a marked transient increase in current during the washout period of high concentrations of pentobarbitone.…”
Section: Discussionmentioning
confidence: 97%
“…It is now generally accepted that a common feature of general anaesthetic agents is positive modulation of the inhibitory function of the neurotransmitter yaminobutyric acid (GABA) through GABAA receptors (Olsen, 1988;Tanelian et al, 1993;Franks & Lieb, 1994;Zimmerman et al, 1994). Electrophysiological and neurochemical studies have shown that general anaesthetic agents can have three mechanisms of action, namely (i) a potentiation of the GABA response (Evans, 1979;Study & Barker, 1981;Lin et al, 1992), (ii) a direct activation of GABAA receptors (Robertson, 1989;Franks & Lieb, 1994) and (iii) at high concentrations, a block of the GABA chloride channel (Schwartz et al, 1986;Peters et al, 1988;Robertson, 1989). The potentiation of the GABA response has been shown to be due to an increase in the ion channel open time (Mathers & Barker, 1980;Study & Barker, 1981;Jackson et al, 1982;Macdonald et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In humans and other mammals, behavioural effects which are typical of positive allosteric modulators of GABA A receptors include anxiolysis, cessation of convulsions, sedation and general anaesthesia (Sieghart, 1995), although some of these effects may result from simultaneous action at other receptor types. Some positive GABA A receptor modulators can also act as agonists on the same receptors when tested at higher concentrations (Robertson, 1989;Franks & Lieb, 1994) and this activity may influence the spectrum of clinical effects observed (Sanna et al, 1999). Most GABA A receptor potentiating compounds, with the notable exception of the benzodiazepine clonazepam, also enhance the action of GABA at native and recombinant insect GABA receptors, although they are often less potent than on GABA A receptors and lack the agonist activity observed at some vertebrate GABA A receptors (Belelli et al, 1996;.…”
Section: Introductionmentioning
confidence: 99%